1999
DOI: 10.1007/s007870050096
|View full text |Cite
|
Sign up to set email alerts
|

Moyamoya disease in a 12-year-old Caucasian boy presenting with acute transient psychosis

Abstract: This paper reports the case of a 12-year-old boy who presented with an acute transient psychosis. Investigations revealed Moyamoya disease with occlusion of the left middle cerebral artery. There was no previous history of transient ischaemic attacks, no history of psychiatric disease, no family history of psychosis and no history of illicit drug use. Although no previous cases of Moyamoya disease with psychosis as the sole presenting feature have been described, we suggest the possibility of a causal link.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…These are isolated cases of manic symptoms; behavioral disorders including hyperactivity, inattention, easy distractibility, inattention, over-talkativeness, poor academic performance, forgetfulness in daily activities, irritability, stubbornness, emotional lability, and temper tantrums; manic symptoms; and cognitive issues. 3 4 5 6 7 8 Psychotic symptom description in context to MMD is scarce. Klasen et al reported the presentation of a 12-year-old boy who presented with acute-onset verbosity, persecutor beliefs, and auditory hallucinations, with no physical or neurological abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These are isolated cases of manic symptoms; behavioral disorders including hyperactivity, inattention, easy distractibility, inattention, over-talkativeness, poor academic performance, forgetfulness in daily activities, irritability, stubbornness, emotional lability, and temper tantrums; manic symptoms; and cognitive issues. 3 4 5 6 7 8 Psychotic symptom description in context to MMD is scarce. Klasen et al reported the presentation of a 12-year-old boy who presented with acute-onset verbosity, persecutor beliefs, and auditory hallucinations, with no physical or neurological abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…He responded to antipsychotics which were continued for 3 months, and the boy was having normal functioning till 1-year follow-up. 6 The second case describes a 23-year-old male with diagnosis of schizophrenia having multiple episodes and increased susceptibility to develop extrapyramidal symptoms with antipsychotics. No apparent neurological deficit was observed; however, he revealed significant difficulties on high-level attention, reasoning, and problem-solving tasks on neuropsychological assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates of hemorrhage reported in several large studies are presented in Table 4. In individual moyamoya patients, neurological symptoms secondary to moyamoya included laryngomalacia [118], hypotension encephalopathy [117], behavioral changes [119], oral and written language deficits [119,128], transient psychosis [121,129,173], hemiplegia [126,131], hearing loss [132], and cognitive difficulties [120]. Movement disorders as symptoms of moyamoya included chorea [122,123], dystonia [124,125], hemifacial spasms [130], and hemiballismus [127].…”
Section: Symptomatologymentioning
confidence: 99%
“…Psychiatric manifestations associated with MMD in children are uncommon. [ 4 ] These include schizophrenia,[ 4 ] acute transient psychosis,[ 5 ] and mania. [ 6 ] Some patients of MMD also show cognitive impairment, learning disability, and attention deficits.…”
mentioning
confidence: 99%